Study the Conception of the Trinity in the Great Commission of the Gospel of Matthew 28:19-20 - Kuncoro, Hagai; Susanto, Susanto; Rimun, Robinson (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
The Bible records differences in the formula of baptism. As Jesus taught in Matthew 28:19, those who believe should be baptized in the name of the Father, the Son, and the Holy Spirit. Meanwhile, in some parts of the Bible, the disciples command every believer to be baptized in the name of Jesus Christ. This study tries to describe the formula of baptism taught by Jesus. It is a descriptive research and used the Bible, books, and journals as the main sources. It is concluded that the formula of baptism in the name of Jesus does not contradictÂ His teachings. However, because Jesus Himself taught that baptism must be in the name of the Father, the Son and the Holy Spirit, in practice, it is better to use the formula He had taught.